2017
DOI: 10.1177/096739111702500506
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Voids in Carbon/Epoxy Laminates and Their Influence on Mechanical Properties

Abstract: Defects, such as voids and delaminations, may significantly reduce the mechanical performance of components made of composite laminates. Distributed voids and porosity are generated during composite processing and are influenced by prepreg characteristics as well as by curing cycle parameters. On the basis of rheological and thermal analyses, as well as observations of laminates produced by different processing conditions, curing pressure appears the most influent factor affecting the void content. This work c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
(25 reference statements)
1
39
0
Order By: Relevance
“…They found the US technique incapable of identifying the voids in their case. For a woven carbon/epoxy composite, Di Landro et al 188 reported a general trend: Similar void contents were measured with micro-CT and density determination, but the values measured with SEM were smaller. They observed a higher discrepancy between the results of the three methods at void contents above 5-6%, attributed to the void orientation effects.…”
Section: Ultrasonic Testingsupporting
confidence: 60%
See 1 more Smart Citation
“…They found the US technique incapable of identifying the voids in their case. For a woven carbon/epoxy composite, Di Landro et al 188 reported a general trend: Similar void contents were measured with micro-CT and density determination, but the values measured with SEM were smaller. They observed a higher discrepancy between the results of the three methods at void contents above 5-6%, attributed to the void orientation effects.…”
Section: Ultrasonic Testingsupporting
confidence: 60%
“…Using the k-means clustering algorithm, they could segment the voxel models into yarns, matrix, and voids, which can be used in creating realistic models of the composite. The voidage in tubular braided Kevlar/epoxy composites was evaluated using micro-CT by Melenka et al 188 They identified and quantified individual voids using MATLAB. A full analysis of void content, size (distribution), and location was performed, of which some results are presented in Void characteristics section.…”
Section: Ultrasonic Testingmentioning
confidence: 99%
“…However, it is vital to remember that modifying the thermomechanical properties by the addition of LC is the result of the simultaneous impact of the following—the presence of rigid lignocellulosic structures; oil migration, which at the same time causes a nucleating effect; the creation of amorphous plasticizing domains in PLA; and a decrease in interfacial interactions between PLA and LC/LCA particles by the accumulation of migrating oil in the interfacial region. The decrease in tanδ is caused by the incorporation of organic rigid structures into the polymeric matrix and by the increase in PLA crystallinity . If we compare the changes of tanδ variations in the range of glass transition, we can observe that LC‐filled composites revealed better damping properties than materials modified with LCA filler, which may be attributed to the plasticizing effect caused by higher amounts of linseed oil in LC.…”
Section: Resultsmentioning
confidence: 96%
“…Analytical expressions were derived to obtain the normal and shear stress distributions in a three-point bending test [17]. Di Landro et al found that defects, such as voids and delaminations, significantly reduced the mechanical performance of components made of composite laminates [18]. The change in mechanical properties like tensile strength and hardness were investigated by changing the percentage composition of carbon by 30%, 35% and 45% in the carbon epoxy composite [19].…”
Section: Introductionmentioning
confidence: 99%